Pengaruh Pemberian Pupuk Bokashi Padat yang difermentasi dengan Waktu Berbeda terhadap Pertumbuhan dan Produksi Rumput Benggala - Siprianus Mau Bere; Oktovianus R. Nahak; Gerson F. Bira (JAS, 2019)
The purpose of this study was to determine the growth and production of Bengal grass treated with solid bokashi fertilizer fermented at different times. The experimental design used was a randomized block design with 4 treatments and 4 replications. The treatment consists of R0 = Control (without bokashi). R1 = Bokashi fertilizer with 14 days fermentation time. R2 = Bokashi fertilizer with 28 days fermentation time. R3 = Bokashi fertilizer with 28 days fermentation time. The variables measured in this study were shoot height, number of leaves, leaf fresh weight and leaf dry weight. The results of the analysis of variance showed that the duration of bokashi fertilizer fermentation significantly (P <0.05) on the growth of Bengal grass shoots, number of Bengal grass leaves, fresh weight of Bengal grass leaves, dry weight of Bengal grass leaves. It was concluded that the fermented bokashi 28 days (R3) produced a plant height of 100.28 cm, a leaf number of 13.94 cm, and a fresh leaf weight of 3525.00 gr, the dry weight of the leaf was 833 gr so that it was better than the fermentation treatment of 14 days, 21 day and Control.